STRATEGI REBRANDING PEMERINTAH KOTA PASURUAN DALAM MENINGKATKAN JUMLAH WISATAWAN: (Studi Kasus Pasuruan Kota Madinah) - Firdaus, Zidane Imanadin; Setiadi, Tatak (Universitas Negeri Surabaya, 2024)
This study aims to identify the rebranding strategy of the Pasuruan City government to increase the number of tourists, focusing on identity, objectives, communication, and coherence. This research uses a qualitative case study method with a constructivist paradigm. The results reveal that Pasuruan City rebranded itself as Kota Madinah by introducing icons such as the Madinah Umbrella and enhancing religious tourism facilities like the tomb of Mbah Hamid and the Jami Mosque. The objectives of this rebranding include increasing tourist visits, attracting investment for tourism infrastructure development, strengthening community participation in social and cultural activities, building a positive image at the national and international levels, and reinforcing the city's cultural identity and religious values. The communication strategy involves creating a strong visual identity with icons like the Madinah Umbrella and a new logo, using the tagline Madinah van Java and promoting through social media. Promotional materials and annual events are used to attract tourists, while collaboration with local communities and cultural organizations strengthens the relationship between the government and the community. The coherence of this strategy aims to make Pasuruan a leading tourist destination that effectively contributes to local trade and industry, as reflected in sustainable regional spatial planning.